Yoga for People With Chronic Pain in a Community-Based Setting: A Feasibility and Pilot RCT - Arlene A. Schmid PhD, OTR, FAOTA, RYT-200; Christine A. Fruhauf PhD; Julia L. Sharp PhD; Marieke Van Puymbroeck PhD, CTRS,FDRT, RYT-200; Matthew J. Bair MD, MS; Jennifer Dickman Portz PhD, MSW (SAGE Publishing, 2019)
The purpose of this feasibility pilot study was to assess benefits of 8 weeks of yoga in people with chronic pain. Participants completed baseline assessments and were randomized to yoga or usual care. Yoga was offered twice a week for 8 weeks. We assessed feasibility and the Brief Pain Inventory (BPI) was the primary outcome, assessing pain-severity and pain interference on daily activities. Eighty-three people were recruited; 67 people completed the study and were included in the analyses. Average age of participants was 50.78 ± 10.43 years and most participants had pain >10 years. The intervention appeared feasible and there were significant improvements ( P < .05) in multiple measures for the yoga group, including a decrease in BPI interference scores from 7.15 ± 1.70 to 6.14 ± 2.21 ( P = .007). There was a significant difference in body responsiveness and pain management scores between groups at 8 weeks. It appears that yoga was feasible and positively influenced multiple outcome measures for people with chronic pain.